Guía avifaunística en la parroquia Cusubamba, cantón Salcedo provincia de Cotopaxi. - Vivanco Carrillo, Evelyn Andreina (2021)
The objective of the present investigation is to know the species of avifauna that exist in the parish of Cusubamba, belonging to the canton Salcedo, of the province of Cotopaxi—giving us a guide to the species recorded. For this purpose, the situational diagnostic employed sources of bibliography information and one visit in situ, determining that the primary economical source is the agricultural activities; no existing projects focused on the development of tourism, but there are natural and cultural attractions. Next meeting, the parish zoning was carried out, four zones were established in different communities for getting information of different places with climatologic conditions, economic activities, and ecosystems. The characteristics of zones were as follows: zone 1 the lower part of the parish where there are trees of eucalyptus and capulí this zone is the most populated, the zone 2 is the middle part where was taken as a reference one eucalyptus forest and zone of the grazing and crops, zone 3 was the upper part of the parish with one fragile ecosystem El Páramo and the zone 4 was one natural lake surrounded of trees of pine and polylepis; this last discarded because a few days of fieldwork no different species were observed in the study area, obtaining only sparrows, turtledoves and blackbirds, species adapted an intervened zones. In the bird watching was applied methods for the birds watching, in this case, was used two methods: point count and intensive search giving as a result twenty-fine species inventoried, the result was in zone 1, eleven species inventoried, the zone 2 with nineteen species and the zone 3 with ten species. There were used instruments for collecting information: field sheet, camera, GPS, binoculars, and the wikiloc app to plot the routes. It was applied the index of Sorensen to know if exist diversity and simulated between zones and giving us the result that the Z1 and Z2 have average similarity (53.33%), the other two comparisons with low similarity Z2 and Z3 (48,27) and the Z1 and Z3 (46,61%). Despite being in a different range of similarity according to the index comparison, it can be observed that the percentage difference is minimal. With the information collected and the used digital tools was built the description guide of the parish avifaunal, a guide is a tool handy and necessary for the bird watchers; inside it, we found the taxonomic information of each species (order, family, species, conservation status, description, and distribution) with photographic taken in the field.